Mitochondrial-targeted near-infrared "dual mode" fluorescent dyes with large Stokes shift for detection of hypochlorous acid and its bioimaging in cell and mice. (August 2020) - Huang, Yongfei; Zhang, Yongbin; Huo, Fangjun; Liu, Yaoming; Yin, Caixia
Abstract: Hypochlorous acid (HClO) as a reactive oxygen species (ROS) played an important role in many pathological and physiological processes. HClO could kill invading pathogens and bacteria in the immune system. But excessive concentrations of HClO may cause many diseases. Near-infrared fluorescent probes have strong tissue penetrating ability, low autofluorescence interference, and broad application prospects in the field of fluorescence imaging research. In this work, we synthesized a new near-infrared (670 nm) "dual-mode" fluorescent dye NSSN based on the benzothiazole framework for the visual detection of HClO. The NSSN had a large Stokes shift (220 nm), good selectivity, ratiometric near-infrared and low detection limit (0.13 μM). In addition, NSSN could achieve mitochondrial target detection of HClO in HeLa cells, also HClO could be visually detected in nude mice by NSSN . Thus NSSN is expected to be used in the early diagnosis of HClO. Graphical abstract: Image 1 Highlights: A near-infrared"dual-mode" fluorescent dyes NSSN based on benzothiazole for HClO was synthesized. The probe showed high selectivity and sensitivity for HClO with a large stokes shift (220 nm). NSSN could achieve mitochondrial target for HClO in HeLa cells and mice imaging.